Sin^4b-cos^4b+cos^2b

Sin^4b-cos^4b+cos^2b
Гость
Ответ(ы) на вопрос:
Гость
(1-cos2b)²/4-(1+cos2b)²/4+(1+cos2b)/2= =1/4-1/2*cos2b+1/4*cos²2b-1/4-1/2*cos2b-1/4*cos²2b+1/2+1/2*cos2b= =1/2-1/2*cos2b
Гость
[latex]sin^4b-cos^4b+cos^2b=\\\\=(sin^2b-cos^2b)\underbrace {(sin^2b+cos^2b)}_1+cos^2b=-cos2b+cos^2b=\\\\=[\, sin^2 \alpha = \frac{1-cos2 \alpha }{2} \; \to \; \; 2sin^2 \alpha -1=-cos2 \alpha \, ]=\\\\=2sin^2b-1+cos^2b=sin^2b-1+(sin^2b+cos^2b)=\\\\=sin^2b-1+1=sin^2b[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы